2016
DOI: 10.1155/2016/2697187
|View full text |Cite
|
Sign up to set email alerts
|

A Unique Case of Pancreatic Mass due to Pancreatic Elastofibromatosis

Abstract: Elastofibroma is a benign tumor of the musculoskeletal system characterized by the abnormal accumulation of elastinophilic fibers. It has been classically described for subscapular region but has been reported in several musculoskeletal sites over the years and rarely even in the GI tract but never in pancreas. We therefore present the case of a 45-year-old female who presented with intermittent abdominal pain. CT of abdomen revealed 1.4 cm pancreatic neck lesion without peripancreatic lymphadenopathy. Endosco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Elastofibroma is the least common lesion. Table 3 summarizes the clinicopathological features of the previously described 13 cases of this type of lesion [ 12 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ], as well as the present one. The age of the patients ranged from 45 to 88 years (mean, 68.5 years; SD 11.2 years; median, 70.5 years).…”
Section: ⧉ Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Elastofibroma is the least common lesion. Table 3 summarizes the clinicopathological features of the previously described 13 cases of this type of lesion [ 12 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ], as well as the present one. The age of the patients ranged from 45 to 88 years (mean, 68.5 years; SD 11.2 years; median, 70.5 years).…”
Section: ⧉ Discussionmentioning
confidence: 93%
“…In other series, some of the patients presented abdominal pain, obstruction, hematochezia, or anemia [ 3 , 4 , 12 ]. Unlike our series, other authors presented a balanced gender ratio, most lesions were found during endoscopic examination in the stomach, colon, or rectum (therefore, polypoid lesions were frequent) [ 6 , 8 ], and most of the cases showed a fibroelastosis pattern [ 8 ].…”
Section: ⧉ Discussionmentioning
confidence: 99%
See 1 more Smart Citation